The Effectiveness of Social Media Usage in Traffic Public Education to Minimize Traffic Violations Among SHS Students in the Lamongan Police Resort - Sastra, Muhammad Farhan Pradiatama (Police Studies Review, 2024)
A significant increase in accident and traffic violation rates occurred in East Java, where in 2023, the accident rate rose by 70 percent, leading to almost a thousand fatalities. There is a need for public awareness, particularly regarding the understanding of traffic rules and activities in traffic to address this issue in the future. This research aims to describe the activities of the traffic education Unit of the Traffic Directorate of Lamongan Police Resort in reducing traffic violations, identify the factors causing traffic violations among SHS students, and describe the effectiveness of the influence of social media in traffic public education for high school students in Lamongan Police Resort. The conceptual framework of this research includes traffic public education (dikmas lantas), traffic education Unit, traffic violations concept, prevention of traffic violations concept, social media concept and effectiveness concept. The theoretical foundation includes management theory, fishbone theory, uses and gratification theory, and sosial media algorithms. This research utilizes a qualitative approach with descriptive analysis as the research type. Data sources consist of primary and secondary data. Data collection techniques involve interviews, observations, and document reviews. Data validity is ensured through data triangulation. Data analysis techniques encompass data reduction, data presentation, and conclusion drawing. The research results indicate that the use of social media in the implementation of traffic public education in Lamongan Police Resort has been conducted but is not yet optimal and does not align with social media algorithms. There are a few factors that affects the understanding of material for traffic safety through social media that consists of internal factors by Lamongan Traffic Police Personnel and internal factors by SHS students itself. Contents used by Lamongan Police Resort don’t consider what kind of contents SHS students are interested in which affects why the social media contents of Lamongan Traffic Police can’t reach SHS students.